Factors Influencing Governance Practices in Rural Public Infrastructure Projects: A Case Study of Rural Road Project in Malaysia - Abdul Latiff, Abdul Muhaimin; Jaapar, Aini; Mat Isa, Che Maznah (International Journal of Sustainable Construction Engineering and Technology, 2021)
Rural public infrastructure projects are essential as a catalyst for balanced development between urban and rural as well as tools for enhancing the living standard of rural poor. This study focuses on the identification of factors that influence the governance practices in a rural road project in Malaysia. A single case study was conducted from the perspective of a stewardship theoretical lens on a rural road project in East Malaysia, and multiple sources of evidence were used for data collection. The study discovered four main factors, namely intrinsic motivation, altruistic empathy, effective leadership, and shared vision that influence project governance practices in this project. Thus, this article contributes to the understanding of interdependencies of these factors, which drives public officials in different project actors for effective delivery in this project context. The study findings are limited concerning the utilization of a single case study related to the rural road project and its contexts.